The prevalence and infection rates of amphistome species in intermediate snail hosts: a systematic review and meta-analysis - Nyagura, Ignore; Malatji, Mokgadi Pulane; Mukaratirwa, Samson (Frontiers in Veterinary Science, 2024)
The systematic review and meta-analysis were conducted to determine the estimates of the prevalence and infection rates of natural and experimental infections of amphistome species in intermediate host snails (IHs) across different continents. A search of peer-reviewed literature on natural and experimental infections of freshwater snails with amphistome species was conducted from four electronic databases from 1984 to 2023. The estimates of the prevalence and/or infection rates were based on 36 eligible peer-reviewed articles, which met the inclusion criteria and reported on natural and experimental infections of amphistome species in freshwater snails. The results showed that a total of 1,67,081 snail species from the peer-reviewed articles were examined for natural infections and 7,659 snail species for experimental infections. The overall pooled prevalence of amphistome infections from naturally infected snails was 2% (95% CI: 0–4), while the overall pooled prevalence of amphistome infections from infections was 40% (95% CI: 18–64). The highest pooled prevalence of natural infection was 3%, which was recorded in Europe (95% CI: 1–7%). The highest overall prevalence of naturally infected amphistome was 6% (95% CI: 0–20%) for Paramphistomum epiclitum. The Americas had the highest pooled prevalence of experimental amphistome infection among freshwater snails (66%; 95% CI: 26–96%). The highest pooled infection rate of 65% (95% CI: 12–100%) was recorded for Paramphistomum cervi in experimental infections. Galba truncatula was the only snail that qualified for meta-analysis for natural infection with Calicophoron daubneyi, with a pooled prevalence of 3% (95% CI: 1–8%). Galba truncatula infected with C. daubneyi and P. cervi, and Bulinus tropicus infected with Calicophoron microbothrium in the experimental infection qualified for the meta-analysis, with an overall infection rate of 66% (95% CI: 34–92%) and 30% (95% CI: 0–74%), respectively. The pooled prevalence of amphistome species infection in the intermediate host (IH) snails based on detection techniques was higher with PCR compared to the dissection and shedding of cercariae. The results from the quality effects model revealed a high heterogeneity and publication bias between studies. This meta-analysis provided valuable insights into the prevalence and infection rates of amphistome species in snail IHs across different geographical regions.